Pertanian masa depan. Pengantar untuk pertanian berkelanjutan dengan input luar rendah - REIJNTJES, Coen (Kanisius, 1999)
Pertanian masa depan. Pengantar untuk pertanian berkelanjutan dengan input luar ...